The Role of Islamic Religious Education Teachers in Overcoming Students' Difficulties in Reading the Qur'an at Al Islam Ngemplak Middle School - Zachro Soleha; Meti Fatimah (Didaktika: Jurnal Kependidikan, 2024)
This study examines the role of Islamic Religious Education (PAI) teachers in overcoming students' difficulties in reading the Qur'an at SMP Al Islam Ngemplak. The main objective of this study is to determine the role of PAI teachers and the obstacles faced in overcoming students' difficulties in reading the Qur'an. This study highlights various factors that influence students' ability to read the Qur'an, including psychological aspects, teaching methods, and learning environments. This study uses a qualitative approach. By taking the object at SMP Al Islam Ngemplak. Interview methods, participant observation, and documentation are used in collecting data in the field. The analysis method used is descriptive qualitative, namely data collection, data presentation, and conclusion. The results show that the role of PAI teachers is very crucial in providing guidance, motivation, and appropriate learning methods. Effective PAI teachers use a student-centered approach, utilize educational technology, and create a conducive learning environment. The findings of this study emphasize the importance of developing the professionalism of PAI teachers and providing ongoing training to improve their pedagogical skills in overcoming students' difficulties in reading the Qur'an. The results of this study are expected to provide insight for educators and stakeholders in efforts to improve the quality of Islamic religious education in schools.